Soundscape Assessment of Aircraft Height and Size - Memoli, Gianluca; Hamilton-Fletcher, Giles; Mitchell, Steve (Frontiers in Psychology, 2018)
It is accepted knowledge that, for a given equivalent sound pressure level, sounds produced by planes are worse received from local communities than other sources related to transportation. Very little is known on the reasons for this special status, including any interactions that non-acoustical factors may have in listener assessments. Here we focus on one of such factors, the multisensory aspect of aircraft events. We propose a method to assess the visual impact of perceived aircraft height and size, beyond the objective increase in sound pressure level for a plane flying lower than another. We utilize a soundscape approach, based on acoustical indicators (dBs, Lmax, background sound pressure level) and social surveys: a combination of postal questionnaires (related to long-term exposure) and field interviews (related to the contextual perception), complementing well-established questions with others designed to capture new multisensory relationships. For the first time, we report how the perceived visual height of airplanes can be established using a combination of visual size, airplane size, reading distance, and airplane distance. Visual and acoustic assessments are complemented and contextualized by additional questions probing the subjective, objective, and descriptive assessments made by observers as well as how changes in airplane height over time may have influenced these perceptions. The flexibility of the proposed method allows a comparison of how participant reporting can vary across live viewing and memory recall conditions, allowing an examination of listeners’ acoustic memory and expectations. The compresence of different assessment methods allows a comparison between the “objective” and the “perceptual” sphere and helps underscore the multisensory nature of observers’ perceptual evaluations and emotive evaluations. In this study, we discuss pro and cons of our method, as assessed during a community survey conducted in the summer 2017 around Gatwick airport, and compare the different assessments of the community perception.